MRCI investigation of different isomers of Ni2O2H2+ - Hübner, Olaf; Himmel, Hans-Jörg (Physical chemistry, chemical physics, 2011)
The geometrical and electronic structures of different isomers of Ni2O2H2+ are investigated by multireference configuration interaction (MRCI) calculations using natural atomic orbital basis sets. The lowest-lying isomer, Ni2(OH)2+, has a rhombic shape with two OH groups bridging the Ni atoms. The next isomer in energetic order with a relative energy of 0.29 eV consists of a linear NiONi(OH2)+ chain. Other structures with a rhombic shape, (NiH)2O2+, with H bound to the Ni atoms have considerably higher energies, above 4 eV. Especially the low-lying isomers are characterised by a large number of low-lying electronic terms. The product Ni2O2H2+ of the reaction of Ni2O2+ with small alkanes is likely to have the rhombic Ni2(OH)2+ structure. The reaction energy of the reaction Ni2O2+ + H2 → Ni2(OH)2+ is estimated to be about −3.5 eV.